IN-VITRO IN VITRO ANGIOTENSIN-CONVERTING ENZYME INHIBITORY ACTIVITY OF ETHYLACETATE FRACTION OF ASPIDOPTERYS INDICA: PHYTOCHEMICAL PROFILING INTEGRATED BY HIGHRESOLUTION LIQUID CHROMATOGRAPHY MASS SPECTROSCOPY AND IN SILICO APPROACH - PULLA UDAYA CHANDRIKA; PEDIREDDI SOBITHA RANI; KANDANAGOLLA SUMALATHA; GADAMSETTI SUSMITHA; AVVARU V KISHORE BABU; MOHD ABDUL HADI (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: Ethyl acetate fraction of the endemic drug Aspidopterys indica (EAAI) was screened for its in vitro angiotensin-converting enzyme (ACE) inhibitory potential. High-resolution liquid chromatography mass spectroscopy high-resolution liquid chromatography mass spectroscopy (HR-LCMS) was used to identify the biologically active metabolites. It was subjected to an in silico docking approach to recognize their molecular-level interactions with the ACE. Methods: Methanol extract was prepared using ultrasonic extraction and fractionated with ethyl acetate by vacuum liquid chromatography. ACE inhibition was tested in vitro by the Cushman-Chung method. Phytochemical profiling of the active fraction was analyzed by HR-LCMS. In addition, in silico molecular docking of identified compounds was performed by AutoDock Vina (PyRx 0.8) to assess the binding affinity to the ACE enzyme. Results: The ethyl acetate fractionated residue from the methanol extract of A. indica was tested for ACE inhibition; the IC50 of EAAI was 117.59 μg/mL, and positive control captopril was 81.56 μg/mL. After comprehensive HR-LCMS analysis, a broad range of 26 remarkable metabolites were identified, including four terpenoids, three flavonoids, three glycosides, two alkaloids, two long-chain amino alcohols, three phenolic acids, one phenolic compound, and two proteins. A glycoside (beta-D-gentiobiosyl crocetin-8.6 kcal), and a flavonoid maritimetin had (−7.8 kcal) demonstrated high binding affinities for 1O86 in a docking study. The findings revealed that EAAI manifested significant ACE inhibition, though less potent than captopril. In silico studies revealed that beta-D-gentiobiosyl crocetin had a binding affinity notably similar to captopril. Conclusion: The ACE inhibition of phytochemicals offers its usage in antihypertensive medications. The present study highlights the substantial potential of A. indica as an ACE inhibitor; it can provide further insights into the research of bioactive components that may align with antihypertensive action.